If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2313x = 12 + -10x Solving -2313x = 12 + -10x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '10x' to each side of the equation. -2313x + 10x = 12 + -10x + 10x Combine like terms: -2313x + 10x = -2303x -2303x = 12 + -10x + 10x Combine like terms: -10x + 10x = 0 -2303x = 12 + 0 -2303x = 12 Divide each side by '-2303'. x = -0.005210594876 Simplifying x = -0.005210594876
| 9.7y-5.7=-1.7 | | 14-8x=64-43x | | 45-4x=14x+21 | | -126-9=9x+18 | | x-3/5= | | 6x+9=-55-10x | | -2y+3(4-y)=12-5y | | x-1/2= | | -27-4x=9-8x | | (6m+8)(6m+4)= | | 5+6z=-11 | | 2x-5=15x+43 | | 2x^3-11x^2-13x=0 | | 34-5x=4x+15 | | 2(x+4)=330 | | -5(x-31)=11.5 | | 19x-4(3x-2)=4 | | 2=8-3x | | 2x+24=10x-56 | | 9x+3-10x-4=24 | | x^4=-81 | | x^4+81=0 | | 7c-3+3=34 | | 6x+39=60x-61 | | (4x)(x+2.5)(x-4.7)=x | | -12x^2+10x+8=0 | | -12x^2+10x+8=0 | | -12x^2+10x+8=0 | | 1.8=x^3 | | e^12x=17 | | 2e^12x=17 | | 3x-4=x+7 |